2019
DOI: 10.2139/ssrn.3425922
|View full text |Cite
|
Sign up to set email alerts
|

The Economics of Artificial Intelligence: A Survey

Abstract: The current advances in Artificial Intelligence are likely to have profound economic implications and bring about new trade-offs, thereby posing new challenges from a policymaking point of view. What is the socioeconomic impact of these new technologies on growth, employment and inequality? How markets and competition will be affected by AI-powered agents? What are the implications in terms of consumers' privacy? Will algorithms reduce consumers' biases or will they rather originate new ones? This work present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 35 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…Employment is another important mechanism through which AI affects an individual's wellbeing, but the empirical results are mixed. For an excellent survey for this topic, readers may refer to Abrardi et al (2019). Acemoglu and Restrepo (2020) calculate that one additional robot per 1000 workers lowers the employment‐population ratio in the US by 0.2 percentage points.…”
Section: What Connects Ai To Wellbeing?mentioning
confidence: 99%
“…Employment is another important mechanism through which AI affects an individual's wellbeing, but the empirical results are mixed. For an excellent survey for this topic, readers may refer to Abrardi et al (2019). Acemoglu and Restrepo (2020) calculate that one additional robot per 1000 workers lowers the employment‐population ratio in the US by 0.2 percentage points.…”
Section: What Connects Ai To Wellbeing?mentioning
confidence: 99%
“…Research has shown that using ML with a high-dimensional vector of consumer features shows profits increased by over 10% (relative to uniform pricing). While consumer surplus declined by less than 1%, nearly 70% of customers are charged less than the uniform price [97,98]. The classic creditworthy characteristics, demographic variables and alternative data captured by consumers' online activity could be used [96,97,99].…”
Section: Efficient Pricingmentioning
confidence: 99%
“…There is a growing consensus on the potential of artificial intelligence to transform modern economies and societies (Abrardi et al 2019;Bolton et al 2018;Boyd and Holton 2017;Makridakis 2017) by enabling computer systems to carry out numerous tasks and activities that are typically considered to require human intelligence, thereby significantly improving efficiency and efficacy. At the same time, there is a controversial debate over the risks and limitations of artificial intelligence.…”
Section: Motivation and Aim Of The Papermentioning
confidence: 99%
“…1 The progress and popularity 2 of artificial intelligence results from the combination of two developments that enable its productive use. The first is that artificial intelligence has matured, thanks to recent advancements in machine learning and deep learning algorithms (Abrardi et al 2019). The second is that the availability of big data combined with the rapidly increasing computation power of modern information technology systems accelerates the development and increases the accuracy of artificial intelligence applications (Allam and Dhunny 2019;Thrall et al 2018).…”
Section: Motivation and Aim Of The Papermentioning
confidence: 99%